Inhibition effects of amino acids on polyphenol oxidase activity isolated from medlar fruit - Ozdemir, Eren; Bilen, Cigdem; Karakus, Emine (SPRINGER, 2025)
In this study, medlar polyphenol oxidase (PPO) was partially purified by (NH4)2SO4 precipitation and dialysis, respectively. The aim of the study was to investigate the inhibition effects of amino acids, which are candidate PPO ligands, on the activity of the medlar PPO enzyme for advanced biochemical purification techniques and to create a usage field for the enzyme inhibitors in different industrial sectors. No any inhibition studies of amino acids have been investigated on medlar PPO in literature yet. Inactivation of PPO is preferred to be prevention of decreasing of nutritional quality and shelf life of foods. Two bands were determined in electrophoresis analyses. Following, amino acids effects were studied on medlar PPO activity to investigate the potentials of Glycine (Gly), L-Phenylalanine (L-Phe), L-Tyrosine (L-Tyr), L-Cysteine (L-Cys), L-Serine (L-Ser), L-Aspartic acid (L-Asp), L-Histidine (L-His), L-Lysine (L-Lys), L-Proline (L-Pro), and L-Methionine (L-Met) whether acting as natural PPO inhibitors. Inhibition types were determined for catechol and L-Cys was found as a potent competitive inhibitor of medlar PPO. While Gly, L-Phe, L-Pro, L-Ser, L-His, and L-Lys showed uncompetitive inhibition; L-Tyr, L-Asp, and L-Met showed mixed-type inhibition. Statistical analysis was performed to understand whether the chemical structure or concentration of inhibitors showing the same type of inhibition made a statistically significant difference on the enzyme activity %. The results showed that the structure of inhibitors did not make a statistically significant difference on the enzyme activity % while inhibitor concentration created significant difference.
Keywords: Mespilus germanica L; Medlar; Polyphenol oxidase; Amino acids; Inhibition; CYSTEINE; PURIFICATION; Biotechnology & Applied Microbiology